The effect of the dietary inclusion of canola oilcake, full-fat canola and sweet lupins on the production performance and fat composition of broilers and pigs - Smith, Natasha (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScAgric (Animal Sciences))--University of Stellenbosch, 2005.